농촌지역 특성 분석 및 유형화-충청남도 읍·면지역을 중심으로-, Characteristic Analysis and Classification of Rural Areas: Based on the Eup and Myon Areas of Chungcheongnam-do - 김정연(Kim Jeong-Youn) (한국지역개발학회지, 충남연구원, 2014)
The objectives of this study are to analyze the characteristics of rural areas and to classify regional types by applying the multi-variate techniques of factor and cluster analyses, with 171 Eup?Myon level data of hungcheongnam-do in 2010. During the process of urbanization and industrialization of rural areas, the differences in location, socio-demographic factors, geo-politics, urbanizing and industrializing patterns in rural areas have been driving or accelerating differentiation of rural areas. Based on the factor analysis, 21 factors of Eup-Myon areas are categorized five principal characteristics as follows: municipal city characteristics, typical paddy farming characteristics, urbanizing rural characteristics, aged farming characteristics, and ndustrializing rural characteristics. According to the cluster analysis, 171 Eup?Myon areas of Chungcheongnam-do are classified as 6 different regional types as follows
Keywords: 농촌지역; rural area; 특성; characteristics; 지역유형; regional type; 지역유형화; regional classification; 분화; differentiation